Rationalization Of The Classical Criticism Of Hadith: Contribution Of Sharīf Ḥātim Al-‘Aunī In Contemporary Hadith Studies - M. Khoirul Huda; Muhammad Reza Fadil (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2023)
This article examines the contributions of Syarif Hatim Al-'Auni in the study of hadith in the contemporary era. One of al-'Auni's contributions is the rationalization of classical hadith criticism. According to al-'Auni, classical hadith criticism works within a rational-universal framework. This has an impact on the acceptance of the classical hadith critique method as a scientific method. This research uses a qualitative-descriptive-analytical approach. The main source of research is the book al-Usus al-'Aqliyyah Li'Ilm Naqd al-Sunnah al-Nabawiyyah. In this context, al-'Auni agrees with Nabia Abbot, Mustafa Azami and Harald Motzki in terms of the reliability of classical hadith criticism methods. On the other hand, Al-'Auni is at odds with scholars who are skeptical of classical hadith criticism methods such as Ignaz Goldziher and Joseph Scacht.